2016
DOI: 10.1590/s1806-37562015000600006
|View full text |Cite
|
Sign up to set email alerts
|

Association between severe asthma and changes in the stomatognathic system

Abstract: Objective:To describe orofacial muscle function in patients with severe asthma. Methods: This was a descriptive study comparing patients with severe controlled asthma (SCA) and severe uncontrolled asthma (SUA). We selected 160 patients, who completed a sociodemographic questionnaire and the 6-item Asthma Control Questionnaire (ACQ-6), as well as undergoing evaluation of orofacial muscle function. Results: Of the 160 patients evaluated, 126 (78.8%) and 34 (21.2%) presented with SCA and SUA, respectively, as def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
3
6
0
2
Order By: Relevance
“…These results are in agreement with the pattern described in the literature, where the temporalis muscles are more active than the masseter muscles (22). The mandibular excursion movements are influenced by the position of the head, peripheral impulses and emotional situations (18). After the mastectomy, functional morbidities are observed, highlighting posture changes that affect the stomatognathic system, mainly in the mandibular kinematics and promoting alterations of the masticatory function (23).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in agreement with the pattern described in the literature, where the temporalis muscles are more active than the masseter muscles (22). The mandibular excursion movements are influenced by the position of the head, peripheral impulses and emotional situations (18). After the mastectomy, functional morbidities are observed, highlighting posture changes that affect the stomatognathic system, mainly in the mandibular kinematics and promoting alterations of the masticatory function (23).…”
Section: Discussionsupporting
confidence: 90%
“…The stomatognathic system, because it is complex, present's well-defined physiological functions, requiring mandible requisition, associated with the movements of structures of the face and neck (18). If a disease occurs in the human body, this system will use adaptive resources to maintain functional efficiency so as not to allow failures to occur, which may be manifested by signs and symptoms of dysfunction (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive research should also be conducted on the relationship between history of DOH and specific evaluation of the orofacial musculature and the performance of spirometry maneuvers in children with respiratory impairment, such as asthma, allergic rhinitis and cystic fibrosis. In the study conducted by Carvalho-Oliveira et al, although on asthmatic adults, there was a high frequency of SS changes, which had an association with the severity of asthma observed by the forced expiratory volume in the first second (FEV 1 ) of spirometry test 25 . Campanha et al performed speech therapy treatment and observed clinical and functional improvement in asthmatic children, evidenced by the increase in the percentage values of the spirometry parameters 26 .…”
Section: Discussionmentioning
confidence: 92%
“…Breathing is one of the vital functions of the organism, where any imbalance can cause numerous changes in various organs and systems. Patients with asthma and rhinitis may present respiratory impairment, resulting in unbalance and adaptations in the musculature and/or orofacial structures and stomatognathic functions, due to the presence of nasal obstruction and consequent mouth breathing (1) . The consequences of this unbalance can be observed in the short or long term, such as facial and vocal quality changes, inadequate occlusion, and body posture alterations (2,3) .…”
Section: Introductionmentioning
confidence: 99%